Language policy in limbo: implications on the quality of english language teachers - Mat Daud, Nuraihan; Md. Zamin, Ainul Azmin; Mat Daud, Nor Shidrah (2010)
The language that is chosen as the medium of communication and instruction is normally more dominant that other languages that are spoken or taught in the country. Thus the language policy adopted by a particular country is of concern especially in places where many languages are spoken, and when there is a need for its population to know a certain language for certain specific reasons. One such country is Malaysia. It has seen a number of changes in its language policy. Bahasa Melayu has been the national and official language since independence in 1957 as documented in the Federal Constitution and the National Language Act. It is a common symbol of identity to integrate the three major ethnic groups which are the Malays, Chinese and Indians into one nation. After Malay was declared the national language in 1967 and the severe race riots in Kuala Lumpur in May 1969 it was decided that English-medium schools would be phased out in Malaysia and by 1985 all former English-medium schools would become Malay-medium schools. In 1994, Malaysia experienced yet another change in its bilingual education when English was adopted as the medium of instruction for scientific and technical courses at the tertiary level. A bolder move was made in May 2002 when English was made the medium of instruction replacing the national language for science and mathematics at schools. Many Malay nationalists, however, lament the move resulting in a decision to move back to Malay in 2009. This paper will discuss the impact of the changes on the potential English language instructors who are the product of the system. Essays produced by those applying for a teaching position at a public university were analysed for this purpose. The study reflects the difficulty in hiring language instructors who are fully proficient in the language.